Dynamic rasterstereography improves the detection of movement delays and dynamic asymmetries in the scapulothoracic kinematic of healthy subjects - Richard Julius Freytag; Jonas Wilhelm Moss; Filippo Maria Piana Jacquot; Jakob Zapatka; Rebecca Herrmann; Mahmoud Ragab; Sebastian Scheidt; Davide Cucchi (Journal of Experimental Orthopaedics)
Abstract Purpose Assessing scapulothoracic kinematics typically involves visually observing patients during movement, which has limited inter‐ and intraobserver reliability. Dynamic rasterstereography (DRS) records, measures and visualizes surface structures in real time, using a curvature map to colour‐code convex, concave and saddle‐shaped structures on the body surface. This study aimed to evaluate the diagnostic efficacy of DRS‐assisted observation in identifying dyskinetic scapulothoracic patterns. Methods Thirty‐seven healthy participants performed shoulder abduction/adduction and flexion/extension cycles without additional weight, recorded using both DRS and a conventional video camera. A metronome ensured consistent timing, and for DRS a grid of parallel light rays projected onto the back surface was captured using indirect optical measurement techniques. The mean surface curvature was converted into a colour scale. The diagnostic performance of conventional and DRS videos in detecting dyskinetic patterns, including static asymmetries, dynamic asymmetries, motion delays and rapid compensatory movements, were compared. Two investigators independently evaluated the videos twice in a blinded and randomized sequence to assess intra‐ and interrater reproducibility. Results Analysis of 118 videos showed good‐to‐excellent intrarater and interrater reproducibility for both techniques (ICCs 0.727–0.949). Movement delays and dynamic asymmetries were observed more frequently when evaluating DRS videos rather than conventional videos (p = 0.0008 and p = 0.0016). However, no differences were found in static asymmetry and rapid compensatory movement detection. Conclusions DRS can create a real‐time model of the trunk surface and allows observers to evaluate the scapular movements with good‐to‐excellent intrarater and interrater reproducibility; compared to clinical observation, some specific scapular motion alterations can be observed more frequently. Clinical Trial Registration: Part of the DRKS00022334 trial. Level of Evidence Level II, prospective cohort study.